IMAGE EFFECT OF HIGHER EDUCATION, SERVICES CAMPUS, EDUCATION LEVEL OF PARENTS AND PROFESSIONALS STUDENTS PARENTS OF INTEREST IN CHOOSING THE DEPARTMENT OF ACCOUNTING STIE MURA CITY LUBUKLINGGAU - Dheo Rimbano (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2016)
This study reviews a student's interest in choosing a major in accounting at STIE MURA Lubuklinggau, the results showed there are significant image of the college, the campus ministry parental education level and profession of parents simultaneously affect the interests of students. Partially There is a positive and significant impact on the image of a college student's interest in selecting accounting majors. The better the image of the university will increase a person's interest to choose a program of study at the university. Partially There is a positive and significant impact on student interest in campus ministry in selecting accounting majors. Improving service quality campus faculty and staff, especially the reliability, responsiveness, treatment of students, an understanding of the interests of students, and the educational facilities provided to students will increase a person's interest to choose a program of study at the university. Partially There is a positive and significant effect of parental education on student interest in choosing a major in accounting. Although students have parents with low education, this does not affect that student interest is also low. And partially are positive and significant influence of the profession of parents of student interest in choosing a major in accounting. Students who have a parent who is a civil servant and non-civil servants to support the student's interest in selecting accounting majors.